The Role of Supply Chain Management on Competitive Advantage and SMEs Operational Performance During Post Pandemic and Digital Era - Arijanto, Rudy (Journal of Industrial Engineering & Management Research, 2022)
This study aims to determine the effect of supply chain management practices on the competitive advantage of SMEs; analyze the effect of supply chain management practices on SMEs performance; determine the effect of competitive advantage on the performance of SMEs . The population in this study was SMEs and the sampling technique in this study used purposive sampling with a sample size of 150 SMEs owners. Data collection techniques used online questionnaires distributed through social media which were tested for validity and reliability. The data analysis tool used to answer the research hypothesis is SmartPLS 3.0. with the stages of testing the validity, reliability, coefficient of termination and hypothesis testing. The results of this study indicate that supply chain management has a direct and positive effect on the competitive advantage of SMEs, supply chain management has a direct and positive impact on the performance of SMEs, competitive advantage has a direct and positive effect on the performance of SMEs. SMEs to continue to improve their competitive advantage and supply chain management to continue to develop their business.